Blood viscosity after splenectomy. Issue 6291 (29th August 1981) - Robertson, D A; Simpson, F G; Losowsky, M S
Abstract : Blood viscosity and its contributory factors–namely, plasma viscosity, fibrinogen concentration, packed cell volume, red-cell deformability, and platelet count–were measured in 20 asymptomatic patients after splenectomy and compared with those in controls. Whole-blood viscosity was significantly increased after splenectomy and was associated with increased platelet count and, more importantly, decreased red-cell deformability. Blood viscosity was measured in six patients before and after splenectomy and in each an increase in viscosity occurred that did not occur in patients who underwent laparotomy without splenectomy. these findings suggest that the inclusions and protein complexes within the red cell that are normally removed by the spleen decrease red-cell deformability and lead to an increase in blood viscosity. This may account for the observed increase in deaths from ischaemic heart disease many years after splenectomy.